Analisis perbedaan faktor-faktor yang berpengaruh terhadap keberadaan jentik Aedes aegypti di kelurahan endemis dan kelurahan sporadis Kota Banjarbaru - Rudi Fakhriadi; Asnawati Asnawati (Balai Litbangkes Tanah Bumbu, 2018)
Dengue Fever (DF) or Dengue Haemorrahagic Fever (DHF) is one of the few infectious diseases that become health problems in the world especially developing countries. Data obtained from Banjarbaru City Health Office found a trend of increasing the incidence of DHF. Last data of 2015 was recorded as many as 182 cases. Of 20 urban villages in Banjarbaru there are 10 outbreaks that menajdi Endemis dengue disease area and 10 outbreaks that became sporadic areas of dengue disease. Dengue fever prevention has a fairly complex problem. But the best way to prevent this disease is by eradicating mosquito larvae The purpose of this study is to see the factors that affect the presence of larva Aedes aegypti in endemic areas and sporadic dengue areas. The design of this study was observational analytic using cross sectional method with 100 samples of house at endemic and sporadic dengue. Data analysis was bivariate with chi-square and multivariate test with logistic regression test with 95% confidence degree. The result of bivariate and multivariate test showed that in the endemic area the related factors were knowledge and community action regarding EMN with larva Aedes aegypti (p <0,05). In the sporadic area of ​​DHF the corresponding variable was community education with the presence of larvae Aedes aegypti (p <0.05). While other variables are not significantly related to the presence of larva Aedes aegypti in endemic and sporadic dengue areas.